Determination of the opinions of science teacher candidates about nanoscience and nanotechnology and their development through activities - Emine Tenekecigil; İshak Afşin Kariper (Scientific Reports)
Abstract This study seeks to explore the perspectives of science teacher candidates on nanoscience and nanotechnology, aiming to enhance their understanding through structured activities. Undergraduate students training to become science teachers were selected as the participants for this research. The study was conducted using a qualitative methodology, with a case study design serving as the framework. Data collection involved semi-structured interviews, observation forms, and questionnaires. Survey and observation data were analyzed descriptively, while interview responses were examined using content analysis. An analysis of existing literature on nanoscience and nanotechnology education revealed that the majority of studies focused on informational presentations, with only a limited number incorporating experimental applications. Acknowledging the importance of embedding nanoscience education into science curricula, this research was structured in two stages: introductory presentations and practical experimental tasks. Following the presentations, participants engaged in experiments on optics and magnetism using nanomaterials, enabling them to directly observe physical changes at the nanoscale. This research presents an innovative approach by combining prior scientific knowledge with hands-on experiments and direct observations to teach nanoscience and nanotechnology concepts. Unlike earlier studies, it integrates nanoscience education with traditional science subjects, making the content more accessible and engaging for learners. The results revealed a significant increase in the interest and awareness of science teacher candidates toward nanoscience and nanotechnology. Additionally, participants strongly advocated for the inclusion of nanoscience education in university curricula, emphasizing its importance in science teaching.